Analysis of the complementarity of intermittent sources in the Brazilian northeast - Lopes da Silva, Stéfany; Maria Alexandre Linard, Fabíola; Rocha Almeida, Aryfrance; Ferreira dos Santos Junior, Bartolomeu (Latin American Journal of Energy Research, 2024)
This study has the objective of generating complementarity maps between the main intermittent sources in the Brazilian Northeast throughout the year, based on the calculation of correlation indices. For this, the study sought to evaluate the energy potential of the region by reproducing maps of potential with renewable sources, including the geolocations of wind, hydroelectric and solar plants already existing in the region, in addition to verifying the correlations on the existence of complementarity between eolian, photovoltaic and hydro resources, through the production of a characteristic year to calculate the correlation indexes that would be visualized through the maps produced by the QGIS software, aiming to demonstrate the complementarity effect between renewable resources in the region. Thus, when analyzing the potential of intermittent sources, it shows that their expansion should be encouraged, where complementary combinations of assets should be encouraged in order to increase the variety and insurability of energy generation. It was also possible to prove that the region has elevated correlation indices and that it can contribute to the expansion of the matrix with the implementation of hybrid plants that can provide energy with more equity during a certain period. And finally, it is observed that practically all existing wind farms can be easily integrated into the solar photovoltaic plant, in addition to the possibility of building a floating solar photovoltaic plant in the reservoir of the hydroelectric plant Pedra do Cavalo, due to the high correlation indices that the region owns, thus using complementarity as the main ally in the supply and generation of energy.
Keywords: Complementarity; Renewable Energy; Power Generation; Complementarity maps; Brazilian northeast